Gambaran Pelaksanaan Kegiatan Pembelajaran di TPA Surau Nurul Iman di Desa Taratak Kenagarian Sungai Abu Kabupaten Solok - Dira Wirdianti; Setiawati Setiawati (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
This research is motivated by the high interest of residents studying in the TPA Surau Nurul Iman in Taratak Kenagarian Sungai Abu, Solok Regency, which shows the high level of attendance, activity and discipline of the learning citizens. Researchers suspect that the cause of the high participation of citizens is due to new innovations. This study aims to describe the implementation of learning activities in the TPA Surau Nurul Iman in Taratak Kenagarian Sungai Abu, Solok Regency. This type of research is quantitative descriptive research. The population in this study were 55 people studying at the TPA Surau Nurul Iman. The sampling technique used was cluster sampling, samples were taken at each level/study group as many as 38 people. Data collection techniques use questionnaires and data collection tools using questionnaires. The data analysis technique uses the percentage formula. The results showed that the implementation of learning activities was seen from sub-variables such as giving material, methods, sources, atmosphere and evaluation categorized as good. This is evidenced by the majority of the learning citizens stating "strongly agree" from each statement given.Keywords: Material, Methods, Learning Resources, Learning and Evaluation, Learning Atmosphere